PENDIDIKAN DALAM PERSPEKTIF HAM - Syukri Ghozali (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Changes that occur in the global world have given birth to a number of challenges, including in the world of education. Humanitarian aspects need to be applied and implemented in a human way in the world of education. Education humanization is an educational process aimed at developing the potential of students as whole people, which is done humanely (humanizing humans), so that students can develop both qualitatively and quantitatively towards perfection. Thus human rights violations in education can be prevented so that the human dignity (Human Dignity) will be maintained and protected, and eventually humans will exist with their existence. But all of this really depends on the good intentions of the education managers and educators to humanize students in the educational process. Finally, hopefully this short article can be an inspiration for millions of education managers and educators to be more human in implementing the education system in their environment, of course by prioritizing humanitarian aspects, because students are humans who must be humanized. Changes that occur in the global world have given birth to a number of challenges, including in the world of education. Humanitarian aspects need to be applied and implemented in a human way in the world of education. Education humanization is an educational process aimed at developing the potential of students as whole people, which is done humanely (humanizing humans), so that students can develop both qualitatively and quantitatively towards perfection. Thus human rights violations in education can be prevented so that the human dignity (Human Dignity) will be maintained and protected, and eventually humans will exist with their existence. But all of this really depends on the good intentions of the education managers and educators to humanize students in the educational process. Finally, hopefully this short article can be an inspiration for millions of education managers and educators to be more human in implementing the education system in their environment, of course by prioritizing humanitarian aspects, because students are humans who must be humanized.